Increasing Efficiency in Extension Using the Train-the-Trainer Approach - Laura A. Warner; Amy Harder; Tom Wichman; Frank Dowdle (EDIS, 2014)
Extension has adapted to today’s financial realities through a number of strategies, including increased reliance on partnerships. One strategy that expands the reach of an Extension agent and capitalizes on partners is the “train-the-trainer” approach. This 4-page fact sheet describes the train-the-trainer approach as it applies to Extension programming, provides contextual examples from within and beyond UF/IFAS Extension, and offers best management practices. Written by Laura A. Warner, Amy Harder, Tom Wichman, and Frank Dowdle, and published by the UF Department of Agricultural Education and Communication, September 2014.